New Knowledge in Information Systems and Technologies Volume 3 - Rocha, Álvaro; Adeli, Hojjat; Reis, Luís Paulo; Costanzo, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book includes a selection of articles from The 2019 World Conference on Information Systems and Technologies (WorldCIST'19), held from April 16 to 19, at La Toja, Spain. WorldCIST is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges in modern information systems and technologies research, together with their technological development and applications. The book covers a number of topics, including A) Information and Knowledge Management; B) Organizational Models and Information Systems; C) Software and Systems Modeling; D) Software Systems, Architectures, Applications and Tools; E) Multimedia Systems and Applications; F) Computer Networks, Mobility and Pervasive Systems; G) Intelligent and Decision Support Systems; H) Big Data Analytics and Applications; I) Human-Computer Interaction; J) Ethics, Computers & Security; K) Health Informatics; L) Information Technologies in Education; M) Information Technologies in Radiocommunications; and N) Technologies for Biomedical Applications.
Breast Cancer Classification with Missing Data Imputation -- Environmental Quality Monitoring System based on Internet of Things for Laboratory Conditions Supervision -- Exploring the Potential of IT-enabled Healthcare in Rural Regions in Cameroon: A Case Study -- Access Control for FHIR Social Care Platforms -- A Framework to Develop Gamified Health Applications -- Computational System for Heart Rate Variability Analysis -- The Gamification in the Design of Computational Applications to Support the Autism Treatments: Partial Results -- Bio-Inspired Petal-Shape UWB Antenna for Indoor Applications -- Applying Safety Methods to Sensor Networks -- Mobile Applications and their use in Language Learning -- Steps Towards Online Monitoring Systems and Interoperability -- Predicting Low Birth Weight Babies through Data Mining -- Virtual Reality in Education: Learning a Foreign Language -- Mobile Crowd Sensing Privacy.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence